Type 2 Diabetes — A Disease of Small Vessels: Clinical Perspectives on Microangiopathy - Dobosz, Maciej; Ignarska, Justyna; Ignarska, Magdalena; Kromer, Agata; Myśliński, Wojciech; Mizerski, Grzegorz (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Type 2 diabetes mellitus (T2DM) is a major cause of microangiopathy, leading to structural and functional impairment of microcirculation. Diabetic microvascular dysfunction underlies key chronic complications, including retinopathy, nephropathy, neuropathy, and cardiomyopathy. The aim of this study was to summarize the pathophysiological mechanisms of diabetic microangiopathy and review current diagnostic methods for microcirculation assessment in T2DM. Review methods: A narrative review of the literature was conducted using PubMed and Google Scholar. Peer-reviewed studies published between 2000 and 2025 addressing microvascular complications of T2DM and diagnostic techniques for evaluating microcirculation were analyzed. State of knowledge: Chronic hyperglycemia induces endothelial dysfunction, basement membrane thickening, increased vascular permeability, and impaired tissue perfusion. These alterations contribute to progressive organ damage, often asymptomatic in early stages. Diagnostic tools range from classical methods such as fundus examination and fluorescein angiography to advanced non-invasive techniques including optical coherence tomography angiography (OCT-A), laser Doppler flowmetry (LDF), capillaroscopy, near-infrared spectroscopy (NIRS), and perfusion MRI. Summary: Early identification of microcirculatory disorders in T2DM is essential to prevent irreversible complications. The development of modern, predominantly non-invasive diagnostic methods increases the potential for earlier detection and improved clinical management.